Development of an NLR-ID Toolkit and Identification of Novel Disease-Resistance Genes in Soybean - Wei Shao; Gongfu Shi; Han Chu; Wenjia Du; Zikai Zhou; Hada Wuriyanghan (Plants, 2024)
The recognition of pathogen effectors through the nucleotide-binding leucine-rich repeat receptor (NLR) family is an important component of plant immunity. In addition to typical domains such as TIR, CC, NBS, and LRR, NLR proteins also contain some atypical integrated domains (IDs), the roles of which are rarely investigated. Here, we carefully screened the soybean (Glycine max) genome and identified the IDs that appeared in the soybean TNL-like proteins. Our results show that multiple IDs (36) are widely present in soybean TNL-like proteins. A total of 27 Gm-TNL-ID genes (soybean TNL-like gene encoding ID) were cloned and their antiviral activity towards the soybean mosaic virus (SMV)/tobacco mosaic virus (TMV) was verified. Two resistance (R) genes, SRA2 (SMV resistance gene contains AAA_22 domain) and SRZ4 (SMV resistance gene contains zf-RVT domain), were identified to possess broad-spectrum resistance characteristics towards six viruses including SMV, TMV, plum pox virus (PPV), cabbage leaf curl virus (CaLCuV), barley stripe mosaic virus (BSMV), and tobacco rattle virus (TRV). The effects of Gm-TNL-IDX (the domain of the Gm-TNL-ID gene after the TN domain) on the antiviral activity of a R protein SRC7TN (we previously reported the TN domain of the soybean broad-spectrum resistance gene SRC7) were validated, and most of Gm-TNL-IDX inhibits antiviral activity mediated by SRC7TN, possibly through intramolecular interactions. Yeast-two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays showed that seven Gm-TNL-IDX interacted with SMV-component proteins. Truncation analysis on a broad-spectrum antiviral protein SRZ4 indicated that SRZ4TIR is sufficient to mediate antiviral activity against SMV. Soybean cDNA library screening on SRZ4 identified 48 interacting proteins. In summary, our results indicate that the integration of IDs in soybean is widespread and frequent. The NLR-ID toolkit we provide is expected to be valuable for elucidating the functions of atypical NLR proteins in the plant immune system and lay the foundation for the development of engineering NLR for plant-disease control in the future.